دور قبیلة ربیعة في تاریخ المشرق في العصر الراشدي والأموي - أ.د.جاسم صكبان علي (College of Education for Women, 2019)
Rabi'a played an important part in the conquer of the east. This tribe had asked to conquer the fareway provinces, in spite of these difficulties, Rabi'a did that and settled in. This tribe was among the opposition of the Umayyad caliphate in the east, because this tribe thinks that the caliphate was with the Mudhariyat and Qaisiat tribes who were their enemies. In spite of that, they were very limited cases in which Rabi'a was the adherence of the caliphate against her enemies like Al-Harith b. Surieg , and were against Qutaiba b. Muslim al- Bahily. Rabi'a assisted Amr b. Muslim movement against the Umayyad governor Qutaibe, because the later wanted to sent her faraway from Mawara al- Nahar. Rabi'a dislikes Nasir b. sayiar who was well known in enmity to Rabi'a and her alliance because of the alliance between Rabi'a and the Yemen they managed to get many victories. The sources mention that some of Rabi'a preferred the Abbasids movement in defiance of Umayyad.